“A Ray of Hope” A Phenomenological Study of Family Caregiver Experiences in Caring for Patients with Parkinson’s Disease - Sugandi, Ekananda; Sawitri, Ni Komang Ari; Krisnawati, Komang Menik Sri; Yanti, Ni Luh Putu Eva (Universitas Muhammadiyah Semarang, 2026)
Patients with Parkinson's disease require long-term care, and family members provide most of this care. This study aims to explore the experiences, feelings, and significance of family members caring for patients with parkinson's disease. This study utilized a qualitative research design with a descriptive phenomenological approach, conducted in Bali in 2025. Semi-structured interviews were performed with six participants, selected through purposive and snowball sampling methods. The data analysis process incorporated interactive analysis, which comprised data collection, condensation, data display, and the formulation of conclusions. The results consist of five main interrelated themes. These themes are family burden vs responsibility, adaptation to a new life, surrender, many roads to Rome, and life expectancy. As the main caregiver, the family experiences many trials, obstacles, emotional changes, financial difficulties, fatigue, and increasing burdens; however, they were able to recover and did not give up on continuing their lives. Medical personnel and local health facilities are expected to collaborate in conducting physical and psychological health assessments for families and providing information about available resources, such as health services and Parkinson's community groups. Healthcare workers are expected to understand, implement preventive measures, and provide solutions to reduce caregiver burden and improve the quality of life for patients with Parkinson's disease and their families.